Trust towards migrants - Néstor Gandelman; Diego Lamé (Inter-American Development Bank (IDB), 2021)
Using a standard trust game, we elicit trust and reciprocity measures in a representative sample of adult players in Montevideo, the capital city of Uruguay, a country that exhibits relatively better levels of tolerance towards migrants than other Latin American countries. We find no statistically significant differences in trust levels of Uruguayans towards countrymen versus migrants. In reciprocity, we find only marginally significant differences attributable to the nationality of the players.
Keywords: C9; J15; 330; Trust; Reciprocity; Experimental games; Migrations